2013
DOI: 10.1074/jbc.m112.369132
|View full text |Cite
|
Sign up to set email alerts
|

Liver Retinol Transporter and Receptor for Serum Retinol-binding Protein (RBP4)

Abstract: Background: Mechanisms by which RBP4 interacts with cells are not completely understood. Results: 1300002K09Rik (RBPR2) is identified as a Stra6-related protein expressed in liver, intestine, and obese fat that mediates RBP4 binding and retinol transport. Conclusion: RBPR2 is a novel RBP4 receptor that mediates retinol uptake. Significance: RBPR2 may be important for whole body retinol homeostasis or cellular actions of RBP4 in certain tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
184
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(193 citation statements)
references
References 70 publications
8
184
0
1
Order By: Relevance
“…It is possible that this protein has a role in intercellular retinol transfer within the liver. Interestingly, Alapatt et al report that RBPR2 shares considerable structural similarity with STRA6 ( 122 ). However, at present, these and other possibilities for explaining how retinol is transported between hepatocytes and HSCs remain to be established.…”
Section: Retinoids In Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that this protein has a role in intercellular retinol transfer within the liver. Interestingly, Alapatt et al report that RBPR2 shares considerable structural similarity with STRA6 ( 122 ). However, at present, these and other possibilities for explaining how retinol is transported between hepatocytes and HSCs remain to be established.…”
Section: Retinoids In Adipose Tissuementioning
confidence: 99%
“…Other early authors suggested that some unidentifi ed protein was involved in facilitating this process ( 6,7,88 ). In late 2012, Alapatt et al reported the identifi cation of a novel retinol transporter that is expressed primarily in mouse liver and intestine and that is able to bind RBP4 (this receptor is named RBP4 receptor-2 or RBPR2) ( 122 ). It is possible that this protein has a role in intercellular retinol transfer within the liver.…”
Section: Retinoids In Adipose Tissuementioning
confidence: 99%
“…3 and 175 ). STRA6, the plasma membrane receptor for retinol carrier RBP4, is known to be induced by atRA in extrahepatic tissues ( 173,174 ) while retinolbinding protein receptor 2 (RBPR2), the recently discovered analogous receptor in rodent liver, is suppressed by atRA, presumably to promote the uptake of retinol by extrahepatic tissues under conditions of vitamin A sufficiency ( 176 ).…”
Section: Feedback Regulation By Atramentioning
confidence: 99%
“…These observations initiated studies leading to the identification of the novel RBP4 receptor-2 (RBPR2) in 2013 [162]. Polymorphisms in RBPR2 have not been investigated so far.…”
Section: Stimulated By Retinoic Acid 6 (Stra6)mentioning
confidence: 99%